(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the newborns in our hospital with fractures of the femur or humerus and their clinical characteristics.Material and Methods: This study was conducted as a retrospective trial and using the patient information system, the following clinical data were reviewed: maternal age, parity, gestational age at delivery (week),fetal weight, pregnancy complications (preeclampsia, gestational diabetes mellitus [GDM]), the type of delivery (cesarean [CS] or vaginal delivery [ VD]), the fetal presentation, labor induction, meconium-stained amniotic fluid, neonatal birthweight and gender, history of shoulder dystocia and intracranial hemorrhage, type of fracture, presence of clavicle fracture or brachial plexus injury, and if has fetal diagnosis and length of hospital stay (day).Results: After the screening, 59622 live births were detected in our hospital in the last 2 years. Long bone fractures were detected in eight of the newborns who were consulted for fractures in the orthopedics department.Femoral fractures were found in 3 patients , humeral fractures in 3patients and both femur and humerus fractures in 2 patients,extra clavicle fracture and brachialplexus injury were detected in two patients.The mean age of the mothers was 29 years ,two patients were diagnosed with gestational diabetes and one patient with severe preeclampsia.Conclusion: The results we found in this study show that long bone fractures are congenital trauma and congenital conditions that require early diagnosis and correct intervention. Especially in the presence of malpresentations and prematurity, the family should be informed about the bone fractures that may develop before cesarean. In addition, careful examination of newborns and avoiding long bone fractures is very important. In our city, these complications are seen with a similar frequency with the literature.